Death Voyage Tradition: Spiritual and Social Values in the Sasak Community's Practices in Sintung Village, Central Lombok, West Nusa Tenggara: Spiritual and Social Values in the Sasak Community's Practices in Sintung Village, Central Lombok, West Nusa Tenggara - Jamiluddin, Jamiluddin; Emilia Fatriani; Lalu Hadi Subandi (TROPICAL WETLAND JOURNAL, 2025)
This study examines the spiritual values embedded in the death voyage rituals practiced by the Sasak community in Desa Sintung, Pringgarata Sub-district, Central Lombok. Rooted deeply in Sasak traditions, these rituals are seen as a means to pray for the deceased's peaceful journey to the afterlife and as social gatherings that strengthen communal bonds within the community. Using a qualitative research method with a descriptive approach, data were collected through in-depth interviews, observations, and documentation. The collected data were analyzed using the data analysis techniques of Miles and Huberman. The findings reveal that the death voyage rituals are conducted on the eighth day after death and continue weekly on the same day until the fortieth day. The rituals encompass various spiritual values, including religious, moral, empirical, and aesthetic elements. These practices remain ongoing and are viewed positively by the community. This study highlights the continuity of these rituals, reflecting the Sasak community's dedication to preserving and practicing their unique cultural identity.